Evaluation of clinical application effect of traditional Chinese medicine fumigation technology on postoperative patients with anorectal diseases - Xie, Tianyang; Zhang, Zichen; Liu, Liu (Vojnosanitetski pregled, 2025)
Background/Aim. Treatment after anorectal surgery plays a key role in wound healing and reducing complications. The aim of this study was to assess the clinical efficacy of traditional Chinese medicine (TCM) fumigation in the postoperative management of anorectal diseases, comparing TCM fumigation with conventional treatments. Methods. This study included 100 anorectal disease patients who underwent surgery at Anhui Chest Hospital, China, from October 2021 to October 2023. The patients were randomly split into two groups – observation and control (50 patients each). TCM fumigation was administered to the observation group, while the control group received potassium permanganate sitz baths. Both groups received 14 days of treatment. The research assessed visual analog scale (VAS), symptom eradication, wound healing, serum substance P (SP) and interferon-gamma (IFN)-γ levels, and therapy efficacy before and after treatment. Side effects were also examined in both groups. Results. The overall effective rate for the observation group was 96%, and for the control group, it was 86%. The observation group’s clinical efficacy exceeded the control group’s clinical efficacy. VAS for pain in both groups dropped after treatment, after which the observation group had lower scores than the control group. The observation group had less anal distension, wound edema, wound fluid, and recovery time than the control group. Within both groups, higher levels of SP and lower levels of IFN-γ in serum were recorded after treatment compared to their pre-treatment values. After treatment, higher levels of SP and lower levels of IFN-γ were recorded in the observed group compared to the control group. The observation group had fewer side effects than the control group (6% vs. 28%). Conclusion. TCM fumigation techniques may increase clinical efficacy, mitigate clinical symptoms, surgical adverse effects, discomfort, and accelerate wound healing following anorectal disorders.
Keywords: fumigation; medicine, chinese traditional; postoperative period; rectal diseases; treatment outcome